Vitamin D3 supplementation alleviates chemically-induced cirrhosis-associated hepatocarcinogenesis - Goto, Renata L. [UNESP]; Tablas, Mariana B. [UNESP]; Prata, Gabriel B. [UNESP]; Espírito Santo, Sara G. [UNESP]; Fernandes, Ana Angélica H. [UNESP]; Cogliati, Bruno; Barbisan, Luis F. [UNESP]; Romualdo, Guilherme R. [UNESP] (Elsevier, 2022)
Vitamin D3 (VD3) deficiency has been associated with increased risk for cirrhosis and hepatocellular carcinoma, a highly incident malignant neoplasia worldwide. On the other hand, VD3 supplementation has shown some beneficial effects in clinical studies and rodent models of chronic liver disease. However, preventive effects of dietary VD3 supplementation in cirrhosis-associated hepatocarcinogenesis is still unknow. To investigate this purpose, male Wistar rats submitted to a combined diethylnitrosamine- and thioacetamide-induced model were concomitantly supplemented with VD3 (5,000 and 10,000 IU/kg diet) for 25 weeks. Liver samples were collected for histological, biochemical and molecular analysis. Serum samples were used to measure 25-hydroxyvitamin D [25(OH)D] and alanine aminotransferase levels. Both VD3 interventions decreased hepatic collagen deposition and pro-inflammatory p65 protein levels, while increased hepatic antioxidant catalase and glutathione peroxidase activities and serum 25(OH)D, without a clear dose-response effect. Nonetheless, only the highest concentration of VD3 increased hepatic protein levels of VD receptor, while decreased the number of large preneoplastic glutathione-S-transferase- (>0.5 mm²) and keratin 8/18-positive lesions, as well the multiplicity of hepatocellular adenomas. Moreover, this intervention increased hepatic antioxidant Nrf2 protein levels and glutathione-S-transferase activity. In summary, dietary VD3 supplementation - in special the highest intervention - showed antifibrotic and antineoplastic properties in chemically-induced cirrhosis-associated hepatocarcinogenesis. The positive modulation of Nrf2 antioxidant axis may be mechanistically involved with these beneficial effects, and may guide future clinical studies.
Keywords: Chemoprevention; Cirrhosis; Diethylnitrosamine; Liver cancer; Thioacetamide; Vitamin D3